Pengaruh Kreativitas Belajar dan Kemandirian Belajar Siswa terhadap Kemampuan Pemecahan Masalah Matematika - Tri Sutrisno; Lin Mas Eva; Condro Endang Werdiningsih (Universitas Indraprasta PGRI, 2019)
The purpose of this study is to analyze the influence of learning creativity and self-reliance learning of mathematical problem-solving skills. The research methods used are surveys. The affordable population in this study is all grade X students of SMK Garuda Nusantara Cikarang Selatan Bekasi school year 2018/2019. The samples in this study were as many as 66 students taken with random sampling techniques. Test normality using the Chi-squared test obtained by all three variables of the normal distribution, the test of linearity using the Fisher test (test F) obtained both linear patterned tests and multicollinearity tests obtained no collinearity/multicollinearity testing hypothesis using double regression acquired double regression equations and Fcount > Ftabel (64.268 > 3.15) meaning Ho Inconclusive: 1) There is an influence between learning creativity and self-reliance learning of mathematical problem-solving ability, 2) there is a significant influence between creativity learning on mathematical problem-solving ability, and 3) there is a significant influence between self-reliance learning on mathematical problem-solving ability